“Cooking and Healthy Girls Club” as alternative education for prevention of stunting for adolescents in Serang Regency - Radifan, Muhamad Almas (BKM Public Health and Community Medicine, 2021)
Objective: This study examines public health problems related to the prevention of stunting and anemia through practical education for young girls, especially with the Cooking and Healthy Girls Club program. Content: Stunting cases in Serang Regency are dominated by middle to lower economic communities who have misunderstandings in the pattern of intake for pregnant women. Problems during adolescence, specifically inadequate nutritional intake and suffering from anemia for a long time will have a negative impact on future mothers. The long-term impact can have a big chance of giving birth to a stunted baby. Young people today like to go on strict diets because they want to have a slim body without thinking about their health. Therefore, the understanding of health for prospective mothers should have been taught a lot and have entered the high school level through the Education Authorities. Early education, especially in the adolescent phase, is the best solution in preventing prolonged stunting. Cooking and Healthy Girls Club can be alternative education that is able to answer problems related to nutrition and health of adolescent girls. In this club program there is collaboration with certain parties who are experts in the fields of culinary, nutrition, and youth health. In this case, it is necessary to involve catering management, foodpreneurs, and KSR PMI (Indonesian Red Cross). The development of health-based youth education programs is not enough with the lecture method alone, but the need for practice and skills, especially in fulfilling nutritious and healthy food. The ability to do business and entrepreneurship is currently a dream for young people. The development of a healthy food business is a potential that needs to be developed by adolescents.